2009
DOI: 10.1136/jnnp.2009.175786
|View full text |Cite
|
Sign up to set email alerts
|

A brain PET study in patients with narcolepsy-cataplexy

Abstract: Hypermetabolism was found in the executive network in narcolepsy at baseline in fully awake condition. Wake state assessment during scanning appears critical to avoid results showing altered functional neurocircuitry secondary to sleepiness and not to the underlying neurological disorder per se. Finally, cataplexy attacks were characterised by a hypometabolism in the hypothalamus associated with wide bilateral brain area hypermetabolisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 26 publications
5
35
0
Order By: Relevance
“…All had low CSF hypocretin-1 level (<110 pg/ml). Seven drug-free patients with NT1 were already included in our previous PET scan study (2). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All had low CSF hypocretin-1 level (<110 pg/ml). Seven drug-free patients with NT1 were already included in our previous PET scan study (2). …”
Section: Methodsmentioning
confidence: 99%
“…For instance, a 18 F-fludeoxyglucose (FDG) positron emission tomography (PET) study reported reduced metabolism in narcolepsy in a wide set of cortico-subcortical areas including the bilateral rectal and subcallosal gyri, the right superior frontal gyrus and inferior parietal lobule, the left supramarginal gyrus, the precuneus bilaterally, and the posterior hypothalamus and mediodorsal thalamic nuclei (3). Using a similar procedure, we found, on the opposite, increased metabolism in the anterior and mid-cingulate cortex, the cuneus, and the lingual gyrus in drug-free patients with narcolepsy–cataplexy scanned in a fully awake condition (2). A more recent PET study found hypometabolism in the right mid-frontal lobe and angular gyrus in young type 1 narcoleptic patients and hypermetabolism in the hippocampus, parahippocampus, amygdala, fusiform, left inferior parietal lobe, left superior temporal lobe, striatum, basal ganglia and thalamus, right hypothalamus, and pons (6).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…11 A positron emission tomographic study has demonstrated shared neural substrates in subjects with narcolepsy/cataplexy. 17 Intravenous procaine activates limbic system structures and produces sensations similar to CPS. 18 Clinical experience suggests that acupuncture can increase as well as decrease activity in the anterior limbic area, especially in the presence of brain pathology.…”
Section: Discussionmentioning
confidence: 99%